(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
We Report the demographic characteristics, laboratory findings, vital signs and outcomes of 19 laboratoryconfirmed COVID-19 patients who admitted to ICU; from 15 Feb to 15 March 2020 in Arak, Markazi Province, Iran. Data showed that the most common laboratory findings on first day of ICU admission, were leukocytosis (52.6%), neutrophilia (73.6%), lymphopenia (100%), anemia (100%), hyperglycemia (78.95), increased levels of INR (100%); AST (66.66%), ALT (50%) and LDH (100%). 36.36% and 45.45% of patients had elevated total and direct bilirubin, respectively but all of patients had normal range of ALK-p (Table 1). In term of vital signs (3 first days); SBP, DBP and PR did not have significant changes but O2 saturation increased from 82.9 % to 93 % and the number of mechanical ventilated patients increased from 36.8% to 73.3%